(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
To acquire clinical expertise in the use of novel sealers for the management of apical periodontitis in permanent teeth. The treatment of chronic apical periodontitis in permanent teeth included root canal obturation with a novel epoxy resin-based sealer and a bioceramic sealer.